For Correlation of Maccabees biblical books and Georgian translations of the hagiographic composition - Jangulashvili, Natia (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2017)
Books of the Maccabees belong to the non-canonic books of the Bible. These books retell about heroic battles fought by Jews. On the basis of these stories hagiographic literature was created which deserves to be explored from a number of points of view. Although the research of the Martyrdom of t Mac- cabees in Georgian has a certain history the monument has not yet been studied from the point of view of literary theory. The article raises the problem of interrelation between theMartyrdom of Maccabees and scriptural books. Based on the overview and study of the more or less complete collections of the Bible existing in our country from historical and philological stand points, we conclude that the Books of Maccabees have been translated much earlier than are currently believed. In particular, one of the Georgian manuscripts of the 10th century (K-1) confirms the existence of the work containing the 4th book of Maccabees. According to the description, a similar text was maintained in the Georgian manuscript preserved at Bodleian Library, Oxford (Bodl. 1). Thus, we propose that these scriptural books were known in Georgia much earlier. Moreover, the Maccabees were translated before they were included into the list of Bakar’s Bible (1743). The Study of the Books of Maccabees II and IV confirm the opinion stated in the scholarly literature that the main content of the hagiographical work was taken from the seventh chapter of the Book II. In our opinion, the hagiographer took into consideration the Book IV of Maccabees to no less extent. Moreover, in the Martyrdom not only many stories and characters but even the phrases coincide with the Biblical text. In the end of discussion of the above-mentioned issues, it is of interest to note that only the Martyrdom contains thename of the martyrs’ mother. In our opinionз this fact provides a basis for the offer that the authors must have em- ployed other sources as well and supposedly, this illustrates that the stories of the martyrs were widespread and of great significance.